Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
Multiple Stressor Effects in Relation to Declining Amphibian Populations 2003
DOI: 10.1520/stp11179s
|View full text |Cite
|
Sign up to set email alerts
|

Ammonium Perchlorate Disruption of Thyroid Function in Natural Amphibian Populations: Assessment and Potential Impact

Abstract: We examined indices of thyroid development in tadpoles from ammonium perchlorate (AP)-exposed sites. Bullfrog (Rana catesbeiana) tadpoles collected from a reference site exhibited normal developmental features, with many completing metamorphoses. In contrast, tadpoles collected from the AP contaminated site exhibited a 5-fold lower hindlimb/snout-vent length ratio than tadpoles from the reference site. The volume of the thyroid gland was 2.5-fold larger in the tadpoles from the reference site, presumably becau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 22 publications
1
18
0
Order By: Relevance
“…The right thyroid was located for each animal and the beginning and end sections were marked. The fifth, middle, and fifth from the last sections were examined for colloid depletion, follicular cell hypertrophy, and follicular cell hyperplasia using a semiquantitative scale as described by Carr et al (2003).…”
Section: Sample Preparation and Histological Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The right thyroid was located for each animal and the beginning and end sections were marked. The fifth, middle, and fifth from the last sections were examined for colloid depletion, follicular cell hypertrophy, and follicular cell hyperplasia using a semiquantitative scale as described by Carr et al (2003).…”
Section: Sample Preparation and Histological Analysismentioning
confidence: 99%
“…Histological examination of thyroid follicles can provide an indication of disruption of thyroid hormone production by xenobiotic chemicals, and has been used to examine thyroid-disrupting effects of a number of different chemicals in fishes Dixon, 1994, 1996;Bhattacharya et al, 1995;Ram, 1998;Ricard et al, 1998;Grinwis et al, 2000;Cooley et al, 2001;Palace et al, 2001;Brown et al, 2004b;Park et al, 2004) and amphibians (Goleman et al, 2002a;Carr et al, 2003). Such toxicant-induced changes are based upon the physiology of the pituitary-thyroid axis.…”
Section: Introductionmentioning
confidence: 99%
“…Ammonium perchlorate is highly water soluble and, because reduction of the central chlorine atom occurs very slowly, can persist in the environment for decades [15]. Surface waters with perchlorate levels in the range of 10 to 30 mg/L [13,16] contained developing frogs with thyroid histopathologic changes, such as follicle cell hypertrophy and colloid depletion [13], that are identical to those reported after laboratory exposure of tadpoles to perchlorate [11,12,14]. Because TH initiates metamorphosis in anuran tadpoles, contaminants such as perchlorate that inhibit TH biosynthesis have the potential to disrupt normal growth and prevent spontaneous metamorphosis [17] and might impair reproductive fitness, leading to adverse effects on amphibian population health.…”
Section: Introductionmentioning
confidence: 99%
“…Work in our laboratory [21] found that AP is not particularly lethal (5‐ and 70‐d median lethal concentrations [LC50s], of 510 ± 36 mg/L and 223 ±13 mg/L, respectively) to developing African clawed frogs ( Xenopus laevis ), but that perchlorate concentrations between 5 and 18 μg/L delayed metamorphosis and concentrations great than 147 μg/L prevented metamorphosis [21]. We have previously exposed X laevis larvae to AP concentrations (59 μg/L, 14 mg/L) [12] at or below those detected at contaminated sites [13,16,22] and found that perchlorate inhibited a number of TH‐dependent indices of development (hindlimb growth) and metamorphosis (forelimb emergence, tail resorption). Additionally, our results indicated that these same concentrations of perchlorate interfered with thyroid function, as evidenced by a reduction in whole‐body T 4 content, which we confirmed by performing simultaneous thyroid epithelial cell height measurements [12].…”
Section: Introductionmentioning
confidence: 99%
“…Histological procedures followed the description of Carr et al (2003). Adult thyroid glands were removed immediately after euthanizing and placed in 10% buffered formalin and stored until preparation (BDE-47: n = 6, control: n = 4).…”
Section: Thyroid Histologymentioning
confidence: 99%